Construction of a recombinant adenovirus co-expressing truncated human prostate-specific membrane antigen and mouse 4-1BBL genes and its effect on dendritic cells - Weng,Xiaodong (2011)
Our aim was to construct a recombinant adenovirus co-expressing truncated human prostate-specific membrane antigen (tPSMA) and mouse 4-1BBL genes and to determine its effect on dendritic cells (DCs) generated from bone marrow suspensions harvested from C57BL/6 mice for which the effect of 4-1BBL on DCs is not clear, especially during DCs processing tumor-associated antigen. Replication deficient adenovirus AdMaxTM Expression System was used to construct recombinant adenovirus Ad-tPSMA-internal ribosome entry site-mouse 4-1BBL (Ad-tPSMA-IRES-m4-1BBL) and Ad-enhanced green fluorescent protein. Day 7 proliferating DC aggregates generated from C57BL/6 mice were collected as immature DCs and further mature DCs were obtained by lipopolysaccharide activated immature DCs. After DCs were exposed to the recombinant adenovirus with 250 multiplicity of infection, the expression of tPSMA and m4-1BBL proteins were detected by Western blot, and the apoptosis and phenotype of DCs were analyzed by flow cytometry. Cytokines (IL-6 and IL-12) in the supernatant were detected by enzyme-linked immunosorbent assay (ELISA). Proliferation of T cells was detected by allogeneic mixed lymphocyte reactions. The tPSMA and m4-1BBL proteins were expressed correctly. The apoptosis rate of DCs transfected with Ad-tPSMA-IRES-m4-1BBL was 14.6%, lower than that of control DCs. The expression of co-stimulatory molecules [CD80 (81.6 ± 5.4%) and CD86 (80.13 ± 2.81%)] up-regulated in Ad-tPSMA-IRES-m4-1BBL-pulsed DCs, and the level of IL-6 (3960.2 ± 50.54 pg/mL) and IL-12 (249.57 ± 12.51 pg/mL) production in Ad-tPSMA-IRES-m4-1BBL-transduced DCs were significantly higher (P < 0.05) than those in control DCs. Ad-tPSMA-IRES-m4-1BBL induced higher T-cell proliferation (OD450 = 0.614 ± 0.018), indicating that this recombinant adenovirus can effectively enhance the activity of DCs.